Lasmiditan for the acute treatment of migraine: Subgroup analyses by prior response to triptans. (January 2020) - Knievel, Kerry; Buchanan, Andrew S; Lombard, Louise; Baygani, Simin; Raskin, Joel; Krege, John H; Loo, Li Shen; Komori, Mika; Tobin, Joshua
Background: Lasmiditan demonstrated superiority to placebo in the acute treatment of migraine in adults with moderate/severe migraine disability in two similarly designed Phase 3 trials, SAMURAI and SPARTAN. Post-hoc integrated analyses evaluated the efficacy of lasmiditan in patients who reported a good or insufficient response to triptans and in those who were triptan naïve. Methods: Subgroups of patients reporting an overall response of "good" or "poor/none" to the most recent use of a triptan at baseline (defined as good or insufficient responders, respectively) and a triptan-naïve subpopulation were derived from combined study participants randomized to receive lasmiditan 50 mg (SPARTAN only), 100 mg or 200 mg, or placebo, as the first dose. Outcomes including headache pain-freedom, most bothersome symptom-freedom, and headache pain relief 2 hours post-first dose of lasmiditan were compared with placebo. Treatment-by-subgroup analyses additionally investigated whether therapeutic benefit varied according to prior triptan response (good or insufficient). Results: Regardless of triptan response, lasmiditan showed higher efficacy than placebo (most comparisons were statistically significant). Treatment-by-subgroup analyses found that the benefit over placebo of lasmiditan did not vary significantly between patients with a good response and those with an insufficient response to triptans. Lasmiditan also showed higher efficacy than placebo in triptan-naïve patients. Conclusions: Lasmiditan demonstrated comparable efficacy in patients who reported a good or insufficient response to prior triptan use. Lasmiditan also showed efficacy in those who were triptan naïve. Lasmiditan may be a useful therapeutic option for patients with migraine. Trial Registration: SAMURAI (NCT02439320); SPARTAN (NCT02605174).